Fear the walking dead? Zombie firms in the euro area and their effect on healthy firms' credit conditions - Lea Katharina Havemeister; Kristian Horn (European Systemic Risk Board (ESRB), European System of Financial Supervision, 2023)
Zombie firms may adversely impact healthy firms through several transmission channels. Besides real spillover effects on productivity or investment, zombies may also cause negative financial spillover effects, where zombies receive credit at more favourable conditions than healthy firms. We investigate characteristics of zombie firms in the euro area and whether they cause spillovers on healthy firms' credit conditions, focusing on two variables: new credit and interest rates. Contrary to existing findings, our results indicate that zombie firms pay higher interest rates and receive less new credit than healthy firms. The spillover effect of zombie firms on healthy firms' new credit is not significant. For interest rates, the spillover effect is even reversed: Zombie existence significantly lowers healthy firms' interest rates. Zombie firms across the euro area are smaller, less profitable, and more leveraged with lower credit quality than healthy firms. Yet, they do not seem to pose significant negative externalities on the credit conditions of healthy firms. Novel loan-by-loan data from the European credit registry (AnaCredit) allows our analysis to be over a broad set of countries and firms, on a new level of granularity. This may explain the divergence of our findings from the existing literature.
Keywords: E43; E44; E51; G21; G32; 330; zombie firms; financial spillovers; interest rates; new credit; financial stability